Employment discrimination due to pregnancy: an analysis of perceptions (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
Pregnancy discrimination is a complex phenomenon that affects labor relations. When a worker becomes pregnant, it generates a lot of tension within the organizational dynamics, due to the consequences for the worker and the obligations contracted by the entity. By virtue of this, the purpose of this study is to learn about the experiences through stories of women who suffered employment discrimination due to pregnancy in Venezuelan organizations. In the methodological aspect, the interpretive paradigm and a qualitative, descriptive approach are assumed, where six key informants who suffered discriminatory acts due to pregnancy participated, in organizations located geographically in Caracas and Miranda State, Venezuela. After applying the interviews, results will be obtained that indicate the existence of psychological, professional and economic affectation in the workers. As well as a systematization of management actions. These results contributed to make this reality visible and open spaces for reflection. In this sense, it is recommended that the people who lead the organizations become aware of the impact of this phenomenon on the victims.
Keywords: employment discrimination; pregnancy; management